Rwanda’s New Companies : An Overview of Registrations, Taxes, Employment and Exports - Savini Zangrandi, Michele; Mogollon, Maria Paulina (World Bank, Washington, DC, 2016)
The Government of Rwanda has introduced several reforms since 2009 that have significantly improved the domestic business environment. One of the reforms is the one-stop shop for business registration. Making use of newly available administrative data sources such as tax and company registrations records, this paper sheds light on the effects of the introduction of the one-stop shop on company registrations, taxes, employment, and exports between 2008 and 2012. The paper finds sizable benefits to Rwandas efforts, which are mostly driven by the registration of large and mid-sized companies, with a limited contribution from small and micro-sized ones. The use of a newly available data source highlights the potential uses of growing bodies of administrative data and their possible shortfalls.